LAMINAR THERMALLY DEVELOPING FLOW INSIDE RIGHT-ANGULARLY TRIANGULAR DUCTS - Aparecido, J. B.; Cotta, R. M. (Kluwer Academic Publ, 1992)
An analytical approach based on the generalized integral transform technique is presented, for the solution of laminar forced convection within the thermal entry region of ducts with arbitrarily shaped cross-sections. The analysis is illustrated through consideration of a right triangular duct subjected to constant wall temperature boundary condition. Critical comparisons are made with results available in the literature, from direct numerical approaches. Numerical results for dimensionless average temperature and Nusselt numbers are presented for different apex angles.